2013
DOI: 10.1155/2013/656158
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Box C/D RNAs Affect Pre-mRNA Maturation in Human Cells

Abstract: Box C/D small nucleolar RNAs (snoRNAs) are known to guide the 2′-O-ribose methylation of nucleotides in eukaryotic ribosomal RNAs and small nuclear RNAs. Recently snoRNAs are predicted to regulate posttranscriptional modifications of pre-mRNA. To expand understanding of the role of snoRNAs in control of gene expression, in this study we tested the ability of artificial box C/D RNAs to affect the maturation of target pre-mRNA. We found that transfection of artificial box C/D snoRNA analogues directed to HSPA8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The analogues of box C/D RNAs were obtained via in vitro transcription according to [ 18 , 19 ]: 28A4518 (98 nt)…”
Section: Methodsmentioning
confidence: 99%
“…The analogues of box C/D RNAs were obtained via in vitro transcription according to [ 18 , 19 ]: 28A4518 (98 nt)…”
Section: Methodsmentioning
confidence: 99%
“…For example, the neuron-specific SNORD115 promotes the inclusion of an alternative exon in the serotonin receptor 2C pre-mRNA (31), and SNORD88C regulates alternative splicing of FGFR3 pre-mRNA (32). Although proof of principle experiments have shown that methylation of the branch point adenosine by engineered snoRNAs can change alternative splicing (33)(34)(35), the mechanism by which SNORDs regulate splice site selection in vivo is not clear.…”
mentioning
confidence: 99%
“…Antisense elements to the branch point, splice donor and acceptor sites, as well as the first and last nucleotides of the intron all resulted in increased alternative splicing and increased production of a known minor isoform of HSPA8 . In a follow‐up study, a subset of these artificial U24 snoRNAs directed at HSPA8 pre‐mRNA were also shown to cause a significant decrease in mRNA levels . As for the snoMEN constructs, this knockdown effect was dependent on the complementary interaction between snoRNA and target, but independent of the ability of the snoRNA to guide methylation of the target …”
Section: Noncanonical Targets and Functions For Snornasmentioning
confidence: 96%
“…In a follow‐up study, a subset of these artificial U24 snoRNAs directed at HSPA8 pre‐mRNA were also shown to cause a significant decrease in mRNA levels . As for the snoMEN constructs, this knockdown effect was dependent on the complementary interaction between snoRNA and target, but independent of the ability of the snoRNA to guide methylation of the target …”
Section: Noncanonical Targets and Functions For Snornasmentioning
confidence: 99%